Executing Upstream Oil and Natural Gas Business Activities: Legal Status and Authority of the Oil and Gas Special Working Unit (SKK) - Armalia Berlinda Irawan; Divka Aulia Esa Riawan (Journal of Sustainable Development and Regulatory Issues, 2023)
The Oil and Gas Special Task Force (SKK Oil) is a government agency responsible for controlling and supervising upstream oil and gas businesses. This study aims to examine the legal position of SKK Oil as the executor of national upstream oil and gas business activities and its role in promoting national energy security. The research utilizes an empirical juridical legal research method with qualitative research specifications, providing a focused and in-depth analysis of the subject matter. Secondary data obtained from primary, secondary, and tertiary legal sources are used in this study. The findings reveal that the National Oil and Gas Management Policy has not fully aligned with the goal of achieving national energy security.